Education in modern Russia : policy and discourse - Zhukova, Olga (2019)
This study examines the ideological processes in the sphere of public education in modern Russia (since 1992) from two sides: the development of the state education policy and the changes in public mind. The purpose is to find the possible inconsistencies between the values, purposes and intentions of those who form the state education policy and those who interact with it (first of all, pedagogic workers and users of educational services). Essential issues in this thesis are how successfully the changes in the legislation can contribute to a real change in the field of education, and whether the ideas approved and promoted by policymakers resonate with the public mind. The study reveals the discrepancy between the state education political guidance and the social realities, which means the need to put more efforts not only in elaboration of good education practices but also in making them commonly accepted.